Antioxidant effect of Physalis angulata fruit on cells exposed to 2,4- dichlorophenoxyacetic acid - Horn, Roberta Cattaneo; GELATTI, GABRIELA TASSOTTI; KOEFENDER, JANA; GOLLE, DIEGO PASCOAL; MAYER, MARIANA SPANEMBERG; HERINGER, TIAGO ANTONIO; PASINI, MAURICIO BATISTELLA; TISSIANI, ANA CAROLINE; ARRUDA, AIME CUNHA; RUBIN, LAURA; RECKTENWALD, RAFAELA DA ROSA; MOREIRA, PAULO RICARDO; et al. (International Journal for Innovation Education and Research, 2019)
Several in vitro studies have described the erythrocyte toxicity mechanism response to the 2,4-dichlorophenoxyacetic acid (2,4-D) and its metabolites, strongly related to oxidative stress. Compounds such as ascorbic acid and flavonoids, present in various fructiferous plants like Physalis angulata L.- Solanaceae, are exogenous sources of antioxidants, which have aroused interest because of its beneficial biological effects to health by capturing oxygen reactive species. Here, was investigated the cytotoxic effects of the 2,4-D in human erythrocytes exposed to this herbicide and treated with the juice of P. angulata fruits. Analyzing the oxidant and antioxidant mechanisms in these cells in vitro, was demonstrated that the damage mechanism by the Physalis juice occurred at the level of cellular proteins and membranes, altering levels of endogenous antioxidants components such as reduced glutathione and uric acid, and exogenous like vitamin C. Our results indicate new insights into the mechanism of human erythrocytes response exposed to the P. angulata juice, providing wayforward to future studies of cytotoxicity.